Psychoanalytic Reading of Unresolved Grief in Sylvia Plath’s ’Daddy’: Electra Complex Manifestations - Jrall, Reecha (Journal of Educational Research and Policies, 2026)
This paper attempts to explore and understand the unconscious of Sylvia Plath by adopting Freud’s psychoanalytical literary criticism to analyse the poem Daddy (1965). Psychoanalytical literary criticism holds literature as a reflection of the unconscious or repressed emotions and desires of the writer. By analysing Plath’s writing this paper attempts to understand the relationship between her literature and her psyche. The paper also analyses Ted Hughes’s The Table and The Shot (1998) to further build on the understanding of Plath’s relationship with her father, Otto Plath. The analysis will essentially contribute to building a greater understanding of her work as a manifestation of her inner psyche or the unconscious. The paper's discourse reinforces the importance of psychoanalytic theory in literary interpretation and in understanding the intricacies of the human intellect.